Expression of Tumor-mediated CD137 ligand in human colon cancer indicates dual signaling effects. (2nd December 2019) - Grimmig, Tanja; Gasser, Martin; Moench, Romana; Zhu, Lang-Jing; Nawalaniec, Karol; Callies, Simone; Wagner, Martin; Polat, Buelent; Mothi, Suraj Sarvode; Luo, Yueming; Ribas, Carmen M.; Malafaia, Osvaldo; et al.
ABSTRACT: CD137-targeting immune therapy, which activates anti-tumor T effector cell responses, seems to be an attractive concept in clinical oncology. Recent evidence has demonstrated that tumor cells besides T cells and antigen-presenting cells are able to express CD137 and CD137L. Here we aimed to identify CD137/CD137L expression in established colon cancer cell lines and primary tumors (UICC stages I-IV) from patients with documented long-term follow-up. CD137/CD137L expression was highly upregulated in early to late-stage tumors while the inverse was observed in patient-derived peripheral blood mononuclear cells. High CD137L expression within primary tumors was mediated by tumor cells and significantly correlated with the occurrence of distant metastases and shortened survival in advanced stages of disease (UICC stage IV). Interestingly, induced tumor cell signaling via CD137L on its surface in vitro resulted in dual effects: (i) reduced tumor cell proliferation suggesting inhibitory signaling in all investigated cancers and (ii) increased epithelial-to-mesenchymal transition signaling events. Taken together CD137/CD137L expression was stage-dependently upregulated with shortened survival in patients with highly CD137L-expressing tumors. Our clinical and experimental data suggest that colon cancer cells predominantly express CD137L and thereby have negative impact on overall survival through a process of reverse signaling. Beside agonistic CD137 antibody therapy to foster T effector cell responses, CD137L-mediated intervention strategies may become instrumental to circumvent relapsed tumor growth through induced epithelial-to-mesenchymal transition and consecutive metastases formation.